Protective effect of Tribulus terrestris on nifedipine induced changes in male sex hormones - Hamid, Sidra; Jamil, Aneela; Khan, Zarmast (Pakistan Journal of Physiology, 2019)
Background: Therapeutic administration of calcium channel blockers (CCBs) has been correlated with iatrogenic male infertility. Any agent that may increase testosterone production and spermatogenesis can be helpful for enhancing fertility in patients taking CCBs. The objective of this study was to determine the protective effect of Tribulus on nifedipine induced changes in serum luteinizing hormone (LH) and testosterone in male rats. Methods: This experimental study was conducted at Shifa College of Medicine, Islamabad in 2014. The study was done on 120 adult male Sprague Dawley rats, divided into 4 groups. Group A received 0.5 ml distilled water once daily orally, group B was administered Nifedipine 50 mg/Kg/rat orally, group C was administered Tribulus aqueous extract 6 mg/Kg/rat once daily, and group D was given both Nifedipine and Tribulus. All doses were given for 8 weeks. After 8 weeks, serum testosterone and serum LH were measured in all groups. Results: The mean serum LH, mean serum testosterone, and p-values for Nifedipine group as compared to the control group were 0.928 and <0.001 respectively; for Tribulus group in regard with the control group were <0.00 and <0.00); for the Nifedipine+Tribulus group were (0.00) and (<0.00) respectively as compared to control group. Nifedipine+Tribulus group had p<0.00 for mean serum LH and p<0.00 for mean serum testosterone, with respect to Nifedipine. Conclusion: Tribulus can be used as a protective drug for the calcium channel blocker induced delirious changes in sex hormones (LH and testosterone) in male rats. Pak J Physiol 2019;15(4):14?6